Sustainable frankincense-modified epoxy/MWCNT biocomposites with tailored mechanical and dielectric properties - Temesgen, Alhayat Getu; Koc, Umit; Kaufmann, Jorg; Aydogmus, Ercan; Cebulla, Holger (Elsevier, 2026)
This study systematically investigates the use of frankincense (Boswellia resin) as a bio-based functional modifier in epoxy/multi-walled carbon nanotube (MWCNT) biocomposites containing castor oil as a renewable plasticizer. Frankincense was incorporated at concentrations of 0-7 wt% into an epoxy matrix containing 0.23 wt% MWCNT and 3 g castor oil. The resulting biocomposites were characterized by bulk density measurements, attenuated total reflectance Fourier-transform infrared (ATR-FTIR) spectroscopy, Shore D hardness, uniaxial tensile testing, frequency-dependent AC electrical conductivity, scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDX), and optical microscopy. The incorporation of frankincense progressively decreased the Shore D hardness from 74 to 64 (13.5%) and the tensile strength from 28.6 to 19.0 MPa (33.6%), while increasing the elongation at break from 5.8% to 9.6% (65.5%), demonstrating a clear transition from brittle to more ductile deformation. ATR-FTIR analysis confirmed the successful incorporation of frankincense through the appearance and enhancement of characteristic carbonyl, hydroxyl, and triterpenoid functional groups, indicating chemical interactions between frankincense and the epoxy network. The AC electrical conductivity increased from approximately 2.5 & times; 10-degrees to 2.7 & times; 10-degrees S cm-1 at 1 MHz (approximate to 8%) with increasing frankincense content, which is attributed to improved MWCNT dispersion and enhanced interfacial polarization. SEM-EDX observations revealed a more homogeneous MWCNT distribution and rougher fracture surfaces at 1-3 wt% frankincense, whereas localized resin-rich domains with particle sizes of approximately 2-30 mu m developed at 5-7 wt% because of partial phase separation. These findings demonstrate that the synergistic incorporation of frankincense and castor oil provides a novel and sustainable strategy for tailoring the mechanical and dielectric performance of epoxy/MWCNT biocomposites, thereby expanding the potential of renewable bio-based materials for multifunctional engineering applications.
Keywords: Frankincense Resin; Epoxy Nanocomposite; Multiwalled Carbon Nanotubes; Bio; Composite; Castor Oil; Electrical Conductivity; Sustainable Materials